Business Intelligence and Data Analysis in the Age of AI - Khan, Arshad (MLI Generative AI Series, 2025)
Unlock data-driven decision-making with Business Intelligence and Data Analysis in the Age of AI. This guide combines traditional BI with AI’s transformative power to help professionals and newcomers excel in the data era. Whether you're a seasoned professional or new to BI, this book provides actionable strategies to navigate the complexities of modern data analysis. Embark on this illuminating journey to master the tools, strategies, and ethical considerations that define modern business intelligence and AI.FEATURES • BI Fundamentals: Master analytics processes and tools• Ethical and Regulatory Challenges: Navigate governance, security, privacy, and ethical frameworks• BI Tools: Learn the power of tools like R, SQL, Python, and data manipulation techniques• Visualize and Predict: Learn data visualization and predictive analytics to forecast trends and drive innovation• Embrace the Future: Discover how AI transforms BI, unlocking new opportunities and navigating emerging risks.